A share in a limited liability company as part of the bankruptcy estate (Ius Novum, 2025)
The article is of a scientific and research nature, and its subject is the determination of the legal status of a share in a limited liability company in the event of the declaration of bankruptcy of the person holding such a share (shareholder). The purpose of the research conducted is to determine the rules governing the management and disposal of shares in the context of a shareholder’s bankruptcy. This requires determining who becomes the subject of the rights under the shares and the executor of these rights at the moment bankruptcy is declared. Given the special nature of bankruptcy laws, it is crucial to determine whether restrictions on the disposition of shares, as provided by the law or the articles of association, are also binding on the receiver. The article demonstrates that the legal status of a share in a limited liability company, and the rights arising from such a share, changes upon the declaration of bankruptcy of a shareholder. Since a share becomes part of the bankruptcy estate, its management and rules of disposal are subordinated to the debt collection function of bankruptcy law. This, in turn, means that certain provisions of the articles of association become ineffective once a shareholder’s bankruptcy is declared and are not binding within the framework of bankruptcy proceedings. The article also demonstrates that the prohibition of offering and promoting the acquisition of shares to an unspecified circle of addressees, as laid down in Article 182¹ of the Commercial Companies Code, is not applicable in bankruptcy proceedings. The paper mainly uses the dogmatic-legal method and critically analyses the views of the doctrine and the positions taken in judicial decisions.